2006
DOI: 10.1103/physrevlett.97.237204
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Evolution of the Conduction-Electron State inCexLa1xB6from Non-Fermi Liquid to Fermi Liquid

Abstract: We report unusual evolution of the conduction-electron state in the localized f electron system CexLa1-xB6 from normal electron state to heavy Fermi liquid (FL) state through local FL and non-FL states with increasing Ce concentration and/or with increasing magnetic field. The effective mass of quasiparticle or the coefficient A of T2 term of resistivity is found to increase divergently near the boundary between FL state and non-FL state. The features of the non-FL state are also different from those of the ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
27
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 19 publications
1
27
1
Order By: Relevance
“…Lanthanum doping of CeB 6 suppresses both AFM and AFQ phases and induces a new multipolar-ordered phase IV beyond a quantum critical point (QCP) at x ≈ 0.3, presumably of octupolar character [57][58][59]. Non-Fermi-liquid behavior has been observed in the vicinity of the QCP [60], and a recent specific-heat investigation of substituted Ce 1−x La x B 6 emphasizes the importance of multipolar fluctuations that are directly linked to the effective mass of charge carriers [61]. However, the nature of the ordered multipoles in phase IV, as well as the underlying interactions [62][63][64][65][66], are still a matter of debate.…”
Section: Introductionmentioning
confidence: 95%
“…Lanthanum doping of CeB 6 suppresses both AFM and AFQ phases and induces a new multipolar-ordered phase IV beyond a quantum critical point (QCP) at x ≈ 0.3, presumably of octupolar character [57][58][59]. Non-Fermi-liquid behavior has been observed in the vicinity of the QCP [60], and a recent specific-heat investigation of substituted Ce 1−x La x B 6 emphasizes the importance of multipolar fluctuations that are directly linked to the effective mass of charge carriers [61]. However, the nature of the ordered multipoles in phase IV, as well as the underlying interactions [62][63][64][65][66], are still a matter of debate.…”
Section: Introductionmentioning
confidence: 95%
“…Correspondingly, it features an AFM phase (phase III) below T N = 2.4 K, which exhibits a complex double-q structure [10] with q 1 = Σ( 2 ). The AFM phase can be suppressed in a magnetic field of B c = 1.05 T [8], however, in contrast to Ce 3 Pd 20 Si 6 , resistivity and heat capacity exhibit Fermi-liquid-like behavior down to the lowest temperatures [11,12], suggesting the absence of fieldinduced quantum-critical fluctuations. Instead, CeB 6 enters an intermediate magnetic phase (phase III ) for B c < B < B Q [8,13].…”
mentioning
confidence: 99%
“…However, the transition at zero temperature occurs into an enigmatic phase IV [16][17][18] instead of the paramagnetic phase (see Fig. 1), also precluding the direct observation of quantum-critical fluctuations in transport properties [11]. The B -T phase diagram as well as the temper- ature and magnetic-field dependencies of the uniform and staggered magnetization could be successfully modeled by a purely localized mean-field Hamiltonian consisting of Zeeman, dipolar, quadrupolar and octupolar exchange terms [19], which suggested that CeB 6 lies far from the critical point where the Kondo effect breaks down.…”
mentioning
confidence: 99%
“…Authors in [1] interpreted the experimental results in frame of the Kondo-impurity approach and pointed out that special attention should be paid to the low concentration limit x ≤ 0.1. At the same time the results of very recent research of resistivity, thermopower, low field Hall coefficient and magnetic susceptibility studies of La 1−x Ce x B 6 (x ≤ 0.1) [2] contradict the predictions of Kondo-impurity approach for these archetypal strongly correlated electron systems in low impurity limit.…”
Section: Introductionmentioning
confidence: 99%
“…Recent discovery of quantum critical behavior in heavy fermion solid solutions La 1−x Ce x B 6 in the range of x ≤ 0.6 [1] has brought renewed interest to study unusual properties of these strongly correlated electron systems. Authors in [1] interpreted the experimental results in frame of the Kondo-impurity approach and pointed out that special attention should be paid to the low concentration limit x ≤ 0.1.…”
Section: Introductionmentioning
confidence: 99%